Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4102/sajhivmed.v20i1.923
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the confidence and knowledge of nurses prescribing antiretroviral treatment in a rural and urban district in the Western Cape province

Abstract: Background Since the introduction of nurse-initiated and managed antiretroviral treatment (NIMART) in South Africa in 2010, initiation of antiretroviral therapy (ART) in primary care has become the responsibility of nurses. The continued success of this approach is dependent on factors such as adequate training and effective support systems. Objectives This study aimed to investigate factors influencing the knowledge and confidence of professional nurses in managing pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…2,18,19 Adequate training results in improved knowledge of HIV management, greater confidence and clinical competence, particularly if accompanied by mentoring. 14,20,21,22 A study conducted in an urban and rural district in the Western Cape found that the majority of NIMART-trained nurses had adequate HIV management knowledge and were very confident to manage adult patients. 22 The survey was specific to adult HIV management as nurses are only involved to a limited extent in the management of children in the Western Cape.…”
Section: Enablers To Nurse-initiated and Managed Antiretroviral Treatmentioning
confidence: 99%
See 3 more Smart Citations
“…2,18,19 Adequate training results in improved knowledge of HIV management, greater confidence and clinical competence, particularly if accompanied by mentoring. 14,20,21,22 A study conducted in an urban and rural district in the Western Cape found that the majority of NIMART-trained nurses had adequate HIV management knowledge and were very confident to manage adult patients. 22 The survey was specific to adult HIV management as nurses are only involved to a limited extent in the management of children in the Western Cape.…”
Section: Enablers To Nurse-initiated and Managed Antiretroviral Treatmentioning
confidence: 99%
“…29 Clinical exposure further contributes to knowledge and confidence as was found in a study conducted in the Western Cape where a higher caseload of HIV patients was associated with higher knowledge and confidence. 22 In the North West province, effective placement, specifically at Community Health Centres, contributed to POE completion. 24 The mentoring of nurses had a positive effect on patient care by improving the clinical skills of professional nurses and by raising the standard of HIV care in the Eastern Cape.…”
Section: Enablers To Nurse-initiated and Managed Antiretroviral Treatmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Longitudinality enhances the completeness attribute, aiming at early and accurate diagnosis in order to initiate Antiretroviral Therapy (ART), as seen in a study conducted in South Africa, in which ART is provided in PHC and prescribed by professional nurses in HIV management, to decrease the viral load in blood circulation, which consequently decreases the spread of the virus. 23 Organizational devices have emerged in the discourses that optimize the RT provision strengthening the attribute of completeness, such as: waiting room and active search, according to the discursive sequences -"prevention activities are done [...] in waiting room care, [...] active search of patients who have and seek the service". Thus, the waiting room constitutes an optimizing space for users to report their daily experiences, reflect on the health-disease process and be sensitized to perform anti-HIV testing.…”
Section: Discursive Fragmentsmentioning
confidence: 99%